Neuropsychiatric symptoms in systemic lupus erythematosus: impact on quality of life. (October 2017) - Monahan, R C; Beaart-van de Voorde, L J J; Steup-Beekman, G M; Magro-Checa, C; Huizinga, T W J; Hoekman, J; Kaptein, A A
Objective: Assess quality of life in patients with systemic lupus erythematosus (SLE) presenting with neuropsychiatric symptoms (neuropsychiatric SLE, NPSLE). Methods: Quality of life was assessed using the Short-Form 36 item Health Survey (SF-36) in patients visiting the Leiden NPSLE clinic at baseline and at follow-up. SF-36 subscales and summary scores were calculated and compared with quality of life of the general Dutch population and patients with other chronic diseases. Results: At baseline, quality of life was assessed in 248 SLE patients, of whom 98 had NPSLE (39.7%). Follow-up data were available for 104 patients (42%), of whom 64 had NPSLE (61.5%). SLE patients presenting neuropsychiatric symptoms showed a significantly reduced quality of life in all subscales of the SF-36. Quality of life at follow-up showed a significant improvement in physical functioning role ( p  = 0.001), social functioning ( p  = 0.007), vitality ( p  = 0.023), mental health ( p  = 0.014) and mental component score ( p  = 0.042) in patients with neuropsychiatric symptoms not attributed to SLE, but no significant improvement was seen in patients with NPSLE. Conclusion: Quality of life is significantly reduced in patients with SLE presenting neuropsychiatric symptoms compared with the general population and patients with other chronic diseases. Quality of life remains considerably impaired at follow-up. Our results illustrate the need for biopsychosocial care in patients with SLE and neuropsychiatric symptoms.